Fluctuating radiocarbon offsets observed in the southern Levant and implications for archaeological chronology debates - Manning, S; Griggs, C; Lorentzen, B; Ramsey, C; Chivall, D; Jull, A; Lange, T (National Academy of Sciences, 2018)
Considerable work has gone into developing high-precision radiocarbon (14C) chronologies for the southern Levant region during the Late Bronze to Iron Age/early Biblical periods (~1200-600 BC), but there has been little consideration whether the current standard Northern Hemisphere 14C calibration curve (IntCal13) is appropriate for this region. We measured 14C ages of calendar-dated tree-rings from AD1610 to 1940 from southern Jordan to investigate contemporary 14C levels and to compare these with IntCal13. Our data reveal an average offset of ~19 14C years, but more interestingly this offset seems to vary in importance through time. While relatively small, such an offset has substantial relevance to high-resolution 14C chronologies for the southern Levant – both archaeological and paleoenvironmental. For example, reconsidering two published studies, we find differences on average of 60% between the 95.4% probability ranges determined from IntCal13 versus those approximately allowing for the observed offset pattern. Such differences affect, and even potentially undermine, several current archaeological and historical positions and controversies.